Improvement of Operational Reliability Resource for JSC “Beltransgaz” Main Pipelines - V. V. Mayorov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers prospects for modernization of the operating linear portion of JSC “Beltransgaz” gas transportation system, various methods and materials which are used while implementing  construction and installation works in the oil and gas sector. It has been shown that in the recent decade one of the most technically, technologically and economically efficient application of the material is double-composite polyurethane coating. The method for coating deposition has been tested and introduced by JSC “Beltransgaz” with significant economic efficiency.